THE THERAPEUTIC EFFICACY OF PHARMACOLOGICAL VERSUS NON-PHARMACOLOGICAL MEASURES IN THE MANAGEMENT OF POST BURN ITCH: Non-Pharmacological Measures in Management of Post Burn Itch - Mumtaz, Firdous; Memon, Abdul Razak; Tahir, S.M.; Shaikh, Bilal Fazal (Pakistan Armed Forces Medical Journal, 2008)
Objective: To standardize the management protocol of post burn itch by comparing therapeutic efficacy of pharmacological with non-pharmacological measures. Study Design: A prospective, clinical investigative and quasi-experimental study. Place & Duration of Study: This study was conducted at Burn emergency Unit, Liaquat University of Medical & Health Sciences Jamshoro for the period of 18 months from January 2006 to June 2007. Patients and Methods: A total of 80 patients were included in the study, and equally divided into 2 groups. Group A received an oral antihistamine with topical Ibuprofen while Group B received olive oil massage followed by wearing of compressive garments. The demographic data and initial assessment of the severity of itch on linear descriptive scale was made by the research team; while subsequent data for the entire study period was obtained by the attending burn clinician who was blind to the allocated regimen. Results were analyzed using computer statistical software SPSS®. Results: Group A included 40 patients with 23 males and 17 females having mean age of 28.13 (SD ± 13.03) and mean body surface area affected 15.387% (SD ± 5.408) and mean itch scale of 5.500 (SD ± 2.219). Group B comprised of 40 patients with 21 males & 19 females with a mean age of 29.38 (SD ± 14.35) with mean affected body surface area of 16.150% (SD ± 5.555) and mean itch scale of 5.350 (SD ± 1.762). The main outcome measure was the improvement in burn itch. The results after 12 weeks of treatment for both groups showed a remarkable improvement in Group B when compared to Group A (p-value 0.000 and 0.365 respectively). Conclusion: The non-pharmacological measures are superior to the pharmacologic measure with respect to their clinical efficacy and their improvement is highly significant after 4 weeks of treatment.